The example of BTJE flow path contamination assessment with anti-icing fluid using statistical models - S. V. Nekrasov; B. A. Chichkov (Научный вестник МГТУ ГА, 2025)
Contamination of the compressor flow path is one of the most prevalent issues encountered during the operation of aircraft gas turbine engines (GTEs). During operation in winter, ingestion of anti-icing fluids and de-icing agents into the compressor flow path presents a substantial risk. In particular, contamination of the compressor rotor blades leads to the reduction in the cross-sectional areas of the inter-blade channels, changes in their shape, and an increase in the roughness of the blade surfaces. All these phenomena compromise compressor performance: result in reduced efficiency, decreased pressure ratio, and airflow, resulting in lower engine thrust, increased jet pipe temperature, higher fuel consumption, reduced gas-dynamic stability, and altered rotor speeds. To eliminate contamination in the gas-air duct during operation, periodic washings of the flow part are performed using solid cleaners, liquid detergents, and water as cleaning agents. The article analyzes changes in deviations of bypass turbo-jet engine recorded parameters from baseline values both when contaminated with anti-icing fluids and after removing contaminants using statistical models based on time series analysis methods, dynamics of model characteristics describing relationships between parameters, as well as synchronization analysis of parameter changes in engines of the same aircraft. The article does not aim to report average parameter change values for a specific engine type and fault but rather demonstrates the principle and effectiveness of the diagnostic method that uses the principle of assessing the dynamics of significance and stability of correlation links between recorded parameters, which are currently underutilized in the scientific-methodological foundations of constructing and applying statistical diagnostic models in operational practice.